Pemanfaatan Pekarangan sebagai Upaya Peningkatan Ketahanan Pangan - Hakim, Aliefman; Kurnia, Ellend Putri; Lasmini, Nurul; Dinata, Ade Nusa Putra; Idmayanti, Idmayanti; Irawanti, Irawanti; Rosida, Rosida; Rosmini, Rosmini; Sakina, Nurul (Universitas Mataram, 2021)
Telaga Baru A is one of the area located in Telaga Bertong Village, Taliwang District, West Sumbawa Regency, West Nusa Tenggara Province, which had not used the house yard to improve the community's economy and national food security. One of the applicable steps that can be applied to optimize the yards of residents is the